Hubungan Faktor Organisasi, Lingkungan, Individu, dengan Stres Kerja pada Karyawan PT. Surgika Alkesindo : The Relationship between Organizational, Environmental, Individual Factors and Work Stress on Employees of PT. Surgika Alkesindo - Sari, Mutia; Yaser, Muhamad (MPI Press, 2022)
Introduction: Stress is a condition where the body's condition is disturbed due to psychological pressure. Usually stress is associated not with physical illness but more with mental illness. Work stress is a condition of tension that affects a person's emotional thinking process and condition. The result is that excessive stress can threaten a person's ability to deal with the environment and will ultimately interfere with the implementation of their duties. According to WHO (World Health Organization) in 2014 in many countries, 8% of work-related illnesses were depression. Research by the Labor Force Survey in 2014 found that there were 440,000 cases of stress due to work in England with an incidence rate of 1380 cases per 100,000 workers who experienced stress due to work. As much as 35% of work-related stress has fatal consequences and it is estimated that lost work days are 43%. Objectives: This research aims to determine the relationship between organizational, environmental, and individual factors with work stress among employees at PT Surgika Alkesindo. Methods: This research uses a cross-sectional design using primary data by distributing questionnaires. The sample in this study were employees at PT Surgika Alkesindo, this sample was taken randomly with a sample size of 133 employees. Results: The results of this research show organizational factors (P value=0.000; OR=23.2), environmental factors (Pvalue=0.000; OR=13.353), and individual factors (Pvalue=0.000). Conclusion: This research can conclude that organizational, environmental, and individual factors are significantly related to work stress in PT Surgika Alkesindo employees.